Case Report: Septic Pericarditis With Achromobacter xyloxidans in an Immunosuppressed Dog - Pascutti, Kristina M.; Dolan, Jacqueline K.; Porter, Lauren T.; Gilor, Shir; Harris, Autumn N. (Frontiers in Veterinary Science, 2022)
A 5-yr-old FS French Bulldog presented for anorexia and increased respiratory rate. On presentation, she was dyspneic with stridor and increased bronchovesicular sounds. Point-of-care ultrasound identified pericardial effusion. Thoracic radiographs identified pleural effusion, a wide cranial mediastinum, and multifocal unstructured interstitial pulmonary opacities. Bloodwork revealed a moderate leukocytosis characterized by a mature neutrophilia with a left shift, hypoalbuminemia, mildly increased alkaline phosphatase activity, and moderate hypokalemia. Thoracic CT findings revealed moderate pericardial and bilateral pleural effusion, mediastinal effusion, and moderate cranial mediastinal lymphadenopathy. Diagnostic thoracocentesis and pericardiocentesis revealed septic exudates with bacilli. Two days later, a median sternotomy and pericardiectomy were performed. Aerobic cultures of the effusions grew Achromobacter xylosoxidans ss deitrificans. The patient was treated with Amoxicillin-clavulanate and enrofloxacin for 12 weeks and clinically fully recovered. Achromobacter xylosoxidans has not been reported as a cause of purulent pericarditis and pyothorax in a dog. Uniquely, this patient is suspected of developing this infection secondary to immunosuppression.